A retrospective case-control study of reasons for referral, main distresses, and goals of care among HIV/AIDS and cancer patients in palliative care - Isabella Soares; Germanus Natuhwera (Scientific Reports)
Abstract As many as 80% of patients receiving palliative care at Hospice Africa Uganda have cancer and/or HIV/AIDS. Given that cancer and HIV/AIDS have different trajectories since antiretroviral therapy (ART) became widely available, these two patients groups may differ in their care needs. This study’s main objective was to identify, summarise and compare the reasons for referral, main distresses, and goals of care among cancer and HIV/AIDS patients in palliative care. A cross-sectional study employing a retrospective design was conducted on 100 consecutively sampled charts consisting of 50 cancer and 50 HIV/AIDS patients. Data were extracted using a researcher-developed structured checklist. Data were entered and analysed in STATA, version 17 using descriptive statistics and Chi-Square (χ2) test. A P-value less than 0.05 was considered statistically significant. The primary reason for referral to palliative care was pain and symptom control at 22 (44%) and 36(72%) among cancer patients and HIV/AIDS patients respectively (χ2 = 8.046, P = 0.005). The most prevalent main distress in both groups was unrelieved pain at 23(46%) in the cancer group versus 24(48%) in the HIV/AIDS group (χ2 = 0.0401, P = 0.841). The most common goal of care was pain and symptom control at 33(66%) and 29(58%) among cancer patients and HIV/AIDS patients respectively (χ2 = 0.6791, P = 0.41). The study findings showed that pain is the most prevalent symptom and the main cause of distress in HIV/AIDs and cancer patients in palliative care. Clinicians need to prioritize pain and symptoms assessment and management in order to optimise quality of life for patients and their families.